Complement activation by recombinant HIV-1 glycoprotein gp120 - Süsal, Caner; Kirschfink, Michael; Kröpelin, M.; Daniel, Volker; Opelz, Gerhard (The journal of immunology, 1994)
The mechanism of CD4+ cell depletion in HIV-infected patients is poorly understood. In this study we investigated whether rgp120 can activate the complement system in the absence of anti-gp120 Abs. We found that the complement proteins C4, C3d, C5b-9, and properdin bind to rgp 120-coated CD4+ T cells of healthy individuals when incubated in autologous serum. Activation of the complement system occurred primarily via the classical pathway and was abolished in sera deficient in C1q and C4 as well as in the presence of EDTA. No cell lysis was observed in a lymphocytotoxicity assay using human serum, possibly because of homologous restriction of complement lysis. In contrast, addition of rabbit sera induced lysis of the rgp 120-precoated cells. Cell lysis by rabbit serum was found to be because of naturally occurring IgM anti-gp 120 Abs. The rgp 120, which was immobilized on the surface of microtiter plates activated complement in the absence of lymphocytes. Complement activation by cell-bound HIV-1 envelope glycoprotein gp120 with subsequent opsonization may be relevant for the elimination of noninfected CD4+ T cells in HIV-infected patients.
Gesehen am 16.06.2021